Analisis Metode Forward Chaining pada Sistem Pakar: Systematic Literature Review - Anisa Maulida; Arisky Rahmatulloh; Irwan Ahussalim; Robby Alvian; Perani Rosyani (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Information technology, which is currently growing rapidly, has now been used in various fields, including psychology, education, agriculture, and health. This motivates professionals to continue building computers with the goal of helping people or even outperforming them. Computer programs called expert systems are created to emulate the knowledge and skills of a human expert on a particular topic. The main goal of an expert system is to offer answers or suggestions that are comparable to those made by human experts. The forward chaining method is one method that can be used to develop expert systems. The decision-making approach known as "chain forward" begins by considering premises or facts before arriving at a final conclusion. By using this method, the system is designed to operate on various devices such as web, mobile or desktop. This study uses the systematics literature review (SLR) methodology, aiming to determine the fields, platforms, as well as the advantages and disadvantages of using the forward chaining method for expert systems that rely on information from related journals between 2018 and 2023.